Building small medium enterprise competitive advantage through situational leadership, digital marketing capabilities and innovation - Muhammad Taufik; Valentino Aris; Rizal Bakri; Farida Islamiah; Husni Mubarak (Manajemen dan Bisnis, 2026)
Small and medium enterprises increasingly need adaptive leadership and digital marketing capabilities to sustain competitiveness in dynamic digital markets. This study examines the influence of situational leadership and digital marketing capability on sustainable competitive advantage among SMEs in Makassar, with digital marketing innovation positioned as a mediating variable. Data were collected from 304 SME owners through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that situational leadership and digital marketing capability significantly enhance digital marketing innovation, with situational leadership emerging as the stronger determinant. Digital marketing innovation and situational leadership were found to exert significant positive effects on sustainable competitive advantage, while digital marketing capability showed no significant direct effect on competitive outcomes. Mediation analysis confirmed that digital marketing innovation significantly mediates both the relationship between digital marketing capability and situational leadership to sustainable competitive advantage. These results suggest that digital marketing capability functions as a strategic prerequisite rather than a direct driver of competitive advantage, and that its value is only realized when actively transformed into innovative marketing practices. The study contributes to the dynamic capabilities literature and extends situational leadership theory by demonstrating that adaptive leadership and digital capabilities must be channeled through innovation to generate sustainable competitive value in resource-constrained SME environments.